2001
DOI: 10.1103/physrevb.63.073107
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of Debye temperature and electron-phonon interaction in1TVSe2

Abstract: Crystals of the layered two-dimensional transition-metal dichalcogenide 1T-VSe 2 are investigated by pointcontact spectroscopy in the charge-density wave state. Relevant characteristics such as mean, root-meansquare, and Debye phonon frequencies are obtained. The Debye temperature is ⌰ D ϭ220Ϯ5 K, close to that of 2H-NbSe 2 . The point-contact function g pc () of the electron-phonon interaction reveals a moderate coupling constant pc ϭ0.27. Consequently, the Coulomb potential, the density of states at the Ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…While no phonon properties of VS 2 have been reported in the literature, it is possible to infer the electron-phonon coupling constant if we assume the validity of the BCS mean-field theory, 24 as was done for VSe 2 . 25 Using the formula that relates the d band binding energy ⑀ 0 = 0.273 eV ͑at the M point͒ to the CDW transition temperature T CDW = 305 K and , k B T CDW = 1.14⑀ 0 e −1/ , we obtain = 0.42, which is larger than that for VSe 2 , consistent with the higher transition temperature of VS 2 . However, we note two important aspects of our data: ͑1͒ given the momentum dependence of ⑀ 0 we obtain a 20% variation in over the Brillouin-zone points probed, a variation that is caused by the momentum dependence of the electronic structure, not of the phonon properties of VS 2 ; ͑2͒ only the vanadium electrons, in the d 1 configuration, form the Fermi surface of VS 2 , while the sulfur bands lie at higher binding energies.…”
Section: B Electron-phonon Couplingmentioning
confidence: 54%
“…While no phonon properties of VS 2 have been reported in the literature, it is possible to infer the electron-phonon coupling constant if we assume the validity of the BCS mean-field theory, 24 as was done for VSe 2 . 25 Using the formula that relates the d band binding energy ⑀ 0 = 0.273 eV ͑at the M point͒ to the CDW transition temperature T CDW = 305 K and , k B T CDW = 1.14⑀ 0 e −1/ , we obtain = 0.42, which is larger than that for VSe 2 , consistent with the higher transition temperature of VS 2 . However, we note two important aspects of our data: ͑1͒ given the momentum dependence of ⑀ 0 we obtain a 20% variation in over the Brillouin-zone points probed, a variation that is caused by the momentum dependence of the electronic structure, not of the phonon properties of VS 2 ; ͑2͒ only the vanadium electrons, in the d 1 configuration, form the Fermi surface of VS 2 , while the sulfur bands lie at higher binding energies.…”
Section: B Electron-phonon Couplingmentioning
confidence: 54%
“…Using mean field theory, we estimated the Curie temperature of the bulk structure to be approximately 39 K and 17 K without a Hubbard-U and with U eff = 1.0 eV, respectively, which is significantly below the charge density transition temperature of 100 -110 K (see Table S1 and the corresponding text in the Supplemental Information). [40][41][42][43][44][45][46] A ferromagnetic ground state is thus not inconsistent with experimental evidence since undistorted 1T-VSe 2 is not stable in the temperature regime in which it would be ferromagnetic.…”
Section: A Stability Of Undistorted Vse2 Layers Withmentioning
confidence: 86%
“…For the 1Tpolytype, T c is predicted to be 35 K for optPBE and U eff = 1.0 eV, and 14 K for optB86b and U eff = 2.5 eV (∆E mag = 11 meV), which is below the experimentally observed charge density wave (CDW) transition temperature of 100 -110 K (onset). [40][41][42][43][44][45][46][52][53][54][55][56] This means that the magnetic transformation in the 1T-structure is unlikely to be observable as the 1T-polytype is unstable at such low temperatures.…”
Section: Monolayer Bilayermentioning
confidence: 99%
See 1 more Smart Citation
“…15 The synthesis and characterization of the layered structure of bulk VSe 2 and its superconducting properties have also been investigated experimentally. 16,17 A recent theoretical study on the electronic and magnetic properties of monolayers of VS 2 and VSe 2 18 concluded that the magnetic properties of these structures can be controlled by applying strain.…”
Section: ■ Introductionmentioning
confidence: 99%